Growth Hormone Deficiency – A Case Report - Devkota, A; Upadhyay, Satyam (Journal of Nepal Paediatric Society, 2011)
Growth hormone is an anabolic hormone released in pulsatile manner in the circulation. It is one of the uncommon causes of short stature in children and is largely idiopathic. The case report is about a 12 years old boy who presented with short stature. He was diagnosed to have Growth hormone deficiency. Growth hormone was started after diagnosis was made. Key words: Growth hormone; pituitary. DOI: 10.3126/jnps.v31i2.3260 J Nep Paedtr Soc 2010;31(2):134-136